Investigasi Eksperimental Anti-Icing System dengan Memanfaatkan Kalor Dari Gas Buang Engine Pesawat Terbang - Joni Kasmara; Gaguk Marausna (Sekolah Tinggi Teknologi Kedirgantaraan, 2020)
Aviation is a high-risk business field. Safety aspects are a top priority to prevent material and non-material losses due to hazards that arise during the flight phase.The stall is one example of a danger that occurs due to the failure of the wing to produce lift.The stall is affected by changes in the wings shape, particularly at the leading edge due to contamination.Contamination occurs in the form of ice particles on the leading edge and regenerates the airflow passing through the wing into turbulent flow.An anti-icing device is needed to overcome this contamination problem by utilizing engine exhaust gas to reduce the consumption of electrical power used in the heating system for the leading edge.Anti-icing design with the helical coil as the main component of the heat exchanger.An experimental method is using to study the effect of the coil diameter ratio on heat transfer characteristics and heat exchanger efficiency.The results showed that the coil diameter ratio affects increasing the secondary flow intensity, creates turbulence flow, increases the heat transfer coefficient, the performance parameters of the heater.